The perceptions of selected Filipino men from allied design fields towards interior design as a profession - Capistrano, Kevin Allan S. (UP College of Home Economics, 2012)
Interior design has been perceived as a woman's profession for the longest time, especially that the profession has been associated with domestic work, as well as the large number of women taking up this field. Thus, several studies had been conducted in the United States, in which the interior design profession was perceived as 'feminine' by the respondents. Thus, men who want to enter design usually take up other related fields such as architecture, industrial design, and the like. Media was also said to have contributed to this kind of misconception. The study sought to determine the perceptions of the selected Filipino men studying in the allied fields of design towards interior design as a profession. Specifically, the study selected architecture, industrial design and industrial engineering students of the University of the Philippines, Diliman through purposive sampling. A survey was conducted among the said students, in order to know their views and opinions about the interior design profession. Results show that there is a common perception towards the interior design profession. Moreover, it is noted that the perceptions of the selected respondents were a bit different from what is predicted at the beginning of the study. The students see the profession beyond its aesthetics component and more than a field reserved for the wealthy few. Findings revealed that the students do not perceive the profession as 'feminine'. This is attributed to their background and exposure to the ideas of interior design, which may also be affected by their training of their chosen fields. These perceptions will be useful for the interior design profession in the country to re-examine their identity as well as establish a more correct view of the profession.